Early Marriage and Human Development Index in Indonesia - Bayu Kharisma; Adhitya Wardhana; Mohammad Zidan Fauzy (Universitas Udayana, 2024)
Early marriage is a violation of children's rights and can have significant negative impacts. Some of the negative impacts of early marriage include physical and mental health risks, barriers to achieving good human resources, and increased risk of maternal and child mortality. This study aims to analyze the determinants of early marriage on the Human Development Index (HDI) using the Geographically Weighted Regression (GWR) method. The estimation results show a significant negative relationship between early marriage and the Human Development Index (HDI), as well as a significant relationship between almost all factors affecting early marriage and HDI, except GRDP per capita, contraceptive use, housing ownership, and child abuse cases. In order to improve human resources and community welfare, the main focus needs to be improving access to education, protecting children's rights, reproductive health, and poverty reduction. Preventing early marriage is key to providing optimal opportunities for children to grow and develop and promoting higher human development.